Link Expiration Time-Aware Routing Protocol for UWSNs. (24th February 2013) - Uddin, Md. Ashraf; Mamun-or-Rashid
Abstract : We propose a link expiration time-aware routing protocol for UWSNs. In this protocol, a sending node forwards a data packet after being sure that the packet reaches the forwarding node, and acknowledgment is returned to the sending node after receiving the data packet. Node mobility is handled in the protocol through the calculation of the link expiration time and sending the packet based on the link expiration time. Although the protocol employs two types of control packet, it provides less energy consumption and at the same time is providing better reliability of packets reaching to the destination because of using acknowledgement packet. The forwarding decision of node is taken by applying Bayes' uncertainty theorem. We use depth, residual energy, and distance from the forwarding node to the sending node as evidence in Bayes' theorem. In this protocol, we use the concept of expert systems ranking potentially true hypothesis. Extensive simulation has been executed to endorse better performance of the proposed protocol.